3-MCPD: A Worldwide Problem of Food Chemistry. Issue 14 (25th October 2016) - Jędrkiewicz, Renata; Kupska, Magdalena; Głowacz, Agnieszka; Gromadzka, Justyna; Namieśnik, Jacek
Abstract : 3-Monochloropropane-1, 2-diol (3-MCPD) is a heat-induced food contaminant that has been widely investigated for decades. This paper presents an overview of current knowledge about 3-MCPD, including its formation routes, occurrence in various foodstuffs, analytical approach, toxicological aspects, and future research perspectives. So far, 3-MCPD was determined in its free and bound form in thermally treated foods, edible oils and fats, and infant foods including human breast milk. Contaminants in infant foods and human breast milk were highlighted in this paper as a serious problem as they can pose a potential hazard for infants. The analytical approach of 3-MCPD determination has been modified for over a decade. Nowadays, the method based on determining the derivative of this compound by using gas chromatography and mass spectrometry is widely used. However, there is still a big need for developing new methods that would produce repeatable results. Some of the toxicologic aspects associated with 3-MCPD still remain unknown. A number of studies on the carcinogenicity and genotoxicity of 3-MCPD were carried out on rodents; however, no clinical studies on humans have been reported so far. Moreover, both detrimental effect on kidneys and antifertility activity have been widely reported. The knowledge of 3-MCPD absorption into body fluids and tissues and its metabolic pathways is based on sometimes conflicting data derived from different studies. In conclusion, although a lot of research has been carried out on 3-MCPD, there is still a need for further research in this area.